Limited Contribution of Small Marine Protected Areas to Regional Biodiversity: The Example of a Small Canadian No-Take MPA - Novaczek, Emilie; Howse, Victoria; Pretty, Christina; Devillers, Rodolphe; Edinger, Evan; Copeland, Alison (Frontiers in Marine Science, 2017)
Over 5,000 marine protected areas (MPAs) exist around the world. Most are small (median size of ~2km2) and designed primarily for the conservation of a single flagship species. Internationally, there is an increasing focus on ecologically representative conservation; however the contribution of these small MPAs to the protection of regional biodiversity is often unknown. This paper presents a benthic habitat mapping exercise and reports on measures of biodiversity in the Eastport MPA and the nearby area of Newman Sound in Eastern Canada. The Eastport MPA is a 2.1km2 no-take reserve designated in 2005, based on a voluntary fishery closure implemented by the local community in 1997. The primary goal of the Eastport MPA is to protect and sustain the American lobster (Homarus americanus) population, supporting a local commercial fishery. Benthic habitats were characterized and mapped using multibeam echosounder data and seafloor videos. Three statistically distinct benthic habitats were identified within the boundaries of the MPA: ‘shallow rocky’, ‘sand and cobble’, and ‘sand’. The distribution of species is primarily driven by depth and substrate type. The shallow rocky habitat (48% of the study area) contains complex bedrock and boulder features with high macroalgal cover. These characteristics are associated with juvenile and adult American lobster habitat. However, comparison of the MPA habitats to the surrounding Newman Sound area indicate that this small MPA contributes little to the conservation of the regional marine biodiversity. We recommend that adaptive management be used to review such MPAs and expand them to better protect ecosystems representative of their regions.